Herbal/Natural Compounds Resist Hallmarks of Brain Aging: From Molecular Mechanisms to Therapeutic Strategies - Juhui Qiao; Chenxi Wang; Yu Chen; Shuang Yu; Ying Liu; Shiting Yu; Leilei Jiang; Chenrong Jin; Xinran Wang; Peiguang Zhang; Daqing Zhao; Jiawen Wang; et al. (MDPI AG, 2023)
Aging is a complex process of impaired physiological integrity and function, and is associated with increased risk of cardiovascular disease, diabetes, neurodegeneration, and cancer. The cellular environment of the aging brain exhibits perturbed bioenergetics, impaired adaptive neuroplasticity and flexibility, abnormal neuronal network activity, dysregulated neuronal Ca2+ homeostasis, accumulation of oxidatively modified molecules and organelles, and clear signs of inflammation. These changes make the aging brain susceptible to age-related diseases, such as Alzheimer's and Parkinson's diseases. In recent years, unprecedented advances have been made in the study of aging, especially the effects of herbal/natural compounds on evolutionarily conserved genetic pathways and biological processes. Here, we provide a comprehensive review of the aging process and age-related diseases, and we discuss the molecular mechanisms underlying the therapeutic properties of herbal/natural compounds against the hallmarks of brain aging.